2007
DOI: 10.4067/s0717-95022007000100016
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries of the Left and Right Temporal Lobes

Abstract: SUMMARY: Anatomical brain asymmetries are subtle and still little studied in humans. Among all the animals, humans have the most asymmetric brains Crow (2004). The language faculty and handedness are localized on the left side. The objective this paper is to verify whether the temporal lobes are anatomically different. Our sample was composed of 40 post mortem adult brains of both sexes, which were investigated at the Human Anatomy Laboratory of the Nove de Julho University Center in São Paulo, Brazil. The bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…The results obtained allows us to sort in ascending order the Psfl as dolicho‐(D), mesati‐ (M), and brachycephalic (B) in both hemispheres, with no statistically significant differences among each brain side, contrary to what was registered between the groups. Consequently, the results obtained suggest that the presence of a significant asymmetry between the right and the left Psf characteristic of humans is not seen in dogs (Tan and Caliskan, ; Heilbroner and Holloway, ; Witelson and Kigar, ; Tan and Kutlu, ; Pilcher et al, ; Boni et al, ; Lui and Kimberley, ) similar to what is describe in some other primates and cats (Yeni‐Komshian and Benson, ; Falk et al, ; Hopkins et al, ; Boni et al, ). Our study demonstrates that although no statistically significant differences were found, it is possible to conclude that the left Psf is bigger than the right one, being this, a common feature in dogs regardless of the type of skull considered.…”
Section: Discussionsupporting
confidence: 66%
“…The results obtained allows us to sort in ascending order the Psfl as dolicho‐(D), mesati‐ (M), and brachycephalic (B) in both hemispheres, with no statistically significant differences among each brain side, contrary to what was registered between the groups. Consequently, the results obtained suggest that the presence of a significant asymmetry between the right and the left Psf characteristic of humans is not seen in dogs (Tan and Caliskan, ; Heilbroner and Holloway, ; Witelson and Kigar, ; Tan and Kutlu, ; Pilcher et al, ; Boni et al, ; Lui and Kimberley, ) similar to what is describe in some other primates and cats (Yeni‐Komshian and Benson, ; Falk et al, ; Hopkins et al, ; Boni et al, ). Our study demonstrates that although no statistically significant differences were found, it is possible to conclude that the left Psf is bigger than the right one, being this, a common feature in dogs regardless of the type of skull considered.…”
Section: Discussionsupporting
confidence: 66%
“…have reported that the distance from the terminal point of the LS to the inferior margin of the ITG in the right hemisphere is 46.86 mm (medium number), and that in the left hemisphere is 44.28 mm (5.95% higher in the right hemisphere). 14 In our study, the distance from the terminal point of the LS to the inferior margin of the ITG was measured as 3.93 ± 0.4300 (mean ± SD) and 4.02 ± 0.4023 cm on the right and left sides, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…For example, the frontal lobe has more 3-hinge and 4-hinge gyri than any other lobes, possibly indicating the more complicated gyrification process in the later stage of neurodevelopment (Brown et al, 2002). Another interesting observation is the left hemisphere shows more foldings than the right hemisphere, both for 3-hinge gyri and 4-hinge gyri, which may indicate more complicated gyrification and functional specification process in the left hemisphere (Sun and Walsh, 2006; Boni et al, 2007). This result reflects the asymmetry of the human brain from a gyral folding perspective.…”
Section: Resultsmentioning
confidence: 99%